Ali Shahab: pelopor sinema elektronik di media televisi Indonesia tahun 1984-2004 - Patoni, Intan Ranti Permatasari; Martha, Nur'aeni; Humaidi, Humaidi (Universitas Negeri Malang, 2024)
Abstract This research aims to explain the role of Ali Shahab as a pioneer of cinema in Indonesian television media for developing television cinema in the period of 1984 to 2004. This research uses historical methods with the descriptive narrative form as using primary sources from Ali Shahab's life history which was wrote by himself for the Indonesian Film Association’s data in 1997, and also using the secondary sources. The results of the research are Ali Shahab pioneered electronic cinema on Indonesian television media with the series